Consumption of iron sources and hemoglobin levels - IV cycle of the nursing E.P of the Universidad Privada de Huancayo Franklin Roosevelt. Huancayo 2018 - Pilco Villagra, María Del Carmen (2020)
Objectives: To determine the relationship between the consumption of iron sources and hemoglobin levels in students of the fourth cycle of the professional nursing school of Roosevelt University. Huancayo 2018. Material and Methods: It is a description of two individual variables that have a correlational relationship and that are not measured in time. Results: According to the results obtained with Rho = 0.483, there is a moderate correlation with a considerable relationship between the consumption of iron sources and hemoglobin levels. There is a moderate correlation between the consumption of heminic iron sources and hemoglobin levels, Rho = 0.512. There is a moderate correlation between the consumption of non-heminic iron sources and hemoglobin levels, Rho = 0.478. There is a slight correlation between the consumption of iron absorption inhibitors and hemoglobin levels, Rho = 0.151. There is a low correlation between the consumption of sources of vitamin C and hemoglobin levels, Rho = 0.347.